2010
DOI: 10.1007/s00542-009-0984-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the effective thermal conductivity of composite materials with FEM based on resistor networks approach

Abstract: In the present paper, a novel and efficient model was developed for predicting the effective thermal conductivity of the composite materials at different filler percentages. By introducing the relative radius as a parameter, the effective thermal conductivity can be predicted precisely when the thermal properties of filler and matrix are prescribed. The model employed the resistor network strategy to achieve a highly efficient prediction during the overall conductivity calculation. To verify this model, a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It was found that the thermal conductivity of polymer-based composites can be efficiently improved by introduction of conductive fillers, and can be influenced by the shape and content of the fillers in matrix [9][10][11][12]. At the same time, various semi-empirical or empirical models have been developed to qualitatively simulate the thermal conductivity of dual-phase polymer matrix composites [13][14][15][16][17][18][19][20][21][22]. There are only few models developed for three-phase cases by Agari et al [17] and Zeng et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the thermal conductivity of polymer-based composites can be efficiently improved by introduction of conductive fillers, and can be influenced by the shape and content of the fillers in matrix [9][10][11][12]. At the same time, various semi-empirical or empirical models have been developed to qualitatively simulate the thermal conductivity of dual-phase polymer matrix composites [13][14][15][16][17][18][19][20][21][22]. There are only few models developed for three-phase cases by Agari et al [17] and Zeng et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we use a numerical model that is based on RRNs to simulate the thermoelectric properties of composites. RRNs can be used as an alternative to state‐of‐the‐art EMTs [ 22,24–29 ] and have proven to be powerful for describing effects from charge transport and heat transport in composite media to fluid flow in porous materials. By discretizing space into finite elements (sites), we model the material as a large linear network.…”
Section: Introductionmentioning
confidence: 99%
“…10,1618 However, PMC’s k eff estimated by these models do not have satisfactory agreement with experimental data when the filler loadings are high. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…10,[16][17][18] However, PMC's k eff estimated by these models do not have satisfactory agreement with experimental data when the filler loadings are high. 18,19 While various experimental studies have been conducted to investigate the effect of fillers on foam morphology 20 and the improvement of electrical and/or mechanical properties by foaming polymer composite and nanocomposite, [21][22][23] studies that investigated the enhancement of PMC's k eff by foaming were scarce. Recently, the fabrication of light-weight thermally conductive linear low density polyethylene (LLDPE)-hexagonal boron nitride (hBN) composite foams with k eff slightly over 3.0 W m -1 K -1 was reported, and the increase in PMC foam's k eff was believed to be attributed to the enhanced alignment of hBN micro-platelets in the LLDPE matrix despite the presence of thermally insulating air voids.…”
Section: Introductionmentioning
confidence: 99%